Sweet Greeks : first-generation immigrant confectioners in the heartland - Beck, Ann Flesor, 1954- (Heartland foodways., 2020)
"Ann Beck is a third-generation Greek confectioner and independent scholar. With her sister, she co-owns and operates Flesor's Candy Kitchen in Tuscola, IL, her grandfather's original business begun in 1901. The sisters have been featured on the CBS Evening News and on regional Illinois PBS stations, as well as in the Chicago Tribune, Los Angeles Times, and American Profile magazine. This project is based on her dissertation completed at the University of Illinois Champaign-Urbana in 2014. Gus Flesor came to the United States from Greece in 1901. His journey led him to Tuscola, Illinois, where he learned the confectioner's trade and opened a business that still stands on Main Street. Sweet Greeks sets the story of Gus Flesor's life as an immigrant in a small town within the larger history of Greek migration to the Midwest. Ann Flesor Beck's charming personal account recreates the atmosphere of her grandfather's candy kitchen with its odors of chocolate and popcorn and the comings-and-goings of family members. "The Store" represented success while anchoring the business district of Gus's chosen home. It also embodied the Midwest émigré experience of chain migration, immigrant networking, resistance and outright threats by local townspeople, food-related entrepreneurship, and tensions over whether later generations would take over the business"--